Impacts of Clinical Pharmacist Intervention on the Secondary Prevention of Coronary Heart Disease: A Randomized Controlled Clinical Study - Xu, Huimin; Zou, Jie; Ye, Xiaoli; Han, Jiayun; Gao, Lan; Luo, Shunbin; Wang, Jingling; Huang, Chunyan; Yan, Xiaofeng; Dai, Haibin (Frontiers in Pharmacology, 2019)
To investigate the impact of clinical pharmacist intervention on the prognosis of acute coronary syndrome (ACS) in Chinese patients with coronary heart disease (CHD). Two hundred and forty patients who had ACS were recruited. Participants were randomly assigned to the intervention group (n = 120) or the control group (n = 120). The intervention group received a medication assessment and education by the clinical pharmacist at discharge and telephone follow-ups at 1 week, 1 month and 3 months after discharge. The control group received usual care. Primary outcomes of this study were the proportion of patients who had major adverse cardiovascular events (MACEs), including mortality, nonfatal myocardial infarction (MI), stroke and unplanned cardiac-related rehospitalizations within 6 and 12 months after hospital discharge. Secondary outcome was self-reported medication adherence to evidence-based medications for CHD (antiplatelets, statins, β-blockers, and angiotensin-converting enzyme inhibitors or angiotensin receptor blockers). Of 240 enrolled patients, 238 (98.3%) completed 6-month follow-up, and 235 (97.9%) completed 12-month follow-up. There were no significant differences between intervention and control groups in the percentages of patients who incurred MACEs within the 6-month follow-up (3.3% vs 7.6%, respectively, P=0.145) or 12-month follow-up (10.9% vs 12.1%, respectively, P=0.783). Significant improvements were found in the prescribing rates of β-blockers and all 4 classes of medications at discharge in the intervention group compared with the control group (P = 0.001 and P = 0.009, respectively). There was no significant difference between intervention and control groups in the use of all 4 classes of medications at the 6-month follow-up (48.3% vs 45.8%, respectively, P=0.691) and 12-month follow-up (47.9% vs 46.6%, respectively, P=0.836). The use of β-blockers was nonsignificantly higher in the intervention group than the control group at the 6-month follow-up (74.2% vs. 64.4%, P = 0.103) and 12-month follow-up (74.8% vs. 63.8%, P = 0.068). Clinical pharmacist intervention had no significant effects on reduction in cardiovascular events among patients with CHD. Further studies with larger sample size and longer time-frame for both intervention and follow-up are needed to validate the role of clinical pharmacist in the morbidity and mortality of CHD.